The Relationship Between Speaking Anxiety and Students' Arabic Speaking Proficiency - Budi Pratama; Haerani Kadar; Yulva Maya Padilah; Busyro Husaini; Rahmah As-Sa’idah; Rizka Salzabila (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2026)
This study aimed to explore the relationship between speaking anxiety and language proficiency of seventh-grade students at Pondok Ulul Albab Yogyakarta using a communicative psycho-sociolinguistic approach. This research employed quantitative design with data analysis techniques using descriptive statistical analysis. The study involved 20 students and utilized observation, interviews, documentation, and a speaking ability test as data collection methods. The assessment covered grammatical accuracy and vocabulary (mean = 65), fluency (mean = 71), content comprehension (mean = 69), and self-confidence (mean = 75). The results of the test showed that 3 students (15%) were very good, 7 students (35%) were good, 6 students (30%) were adequate, and 4 students (20%) were poor. Four main factors contributing to speaking anxiety were identified: students’ social background, the boarding school’s language coaching system, psychological mechanisms of anxiety, and the impact of anxiety on language competence. This study concluded that speaking anxiety is negatively correlated with Arabic language proficiency among seventh-grade students at Pondok Ulul Albab Yogyakarta, such that the higher the students' anxiety, the lower their language proficiency and vice versa.